A haplotype-resolved and chromosome-scale genome assembly of Hainan muntjac (Muntiacus nigripes) - Yilin Cui; Yakui Lv; Jialing Li; Mingjiang Cai; Xi Liu; Zejun Xu; Hui Liu (Scientific Data)
Abstract The Hainan muntjac (Muntiacus nigripes) is a wild animal endemic to Hainan, China. Its species distribution and the diversity of muntjac karyotypes have attracted much attention. Although genomic resources have increased in recent years, relevant genome assembly data of Hainan muntjac are still lacking. Meanwhile, molecular evidence for the taxonomic units of this species remains lacking. In this study, we successfully assembled the Hainan muntjac haplotype genome at the chromosome level using Pacbio long read and long sequencing technologies and Hi-C data. The final assembly size was 2.66 Gb, with allele and scaffold N50 values of 29.27 and 700.27 Mb, respectively, and we scaffolded the genome sequence onto three chromosomes. The genome contains a total of 21,451 genes and 10,056 gene families. Phylogenetic analysis using single-copy gene families revealed that Hainan muntjac is most closely related to red muntjac, with a divergence time of 8–11 Ma. This new genomic resource of Hainan muntjac will be crucial for future comparative genomic analyses and genetic evolutionary studies.